Mrs. Wiggins - Monroe, Mary (Dafina, an imprint of Kensington Publishing Corp., 2021)
"The daughter of a prostitute mother and an alcoholic father, Maggie Franklin knew her only way out was to marry someone upstanding and church-going. Someone like Hubert Wiggins, the most eligible man in Lexington, Alabama--and the son of its most revered preacher. Proper and prosperous, Hubert is glad to finally have a wife, even one with Maggie's background. For Hubert has a secret he desperately needs to stay hidden. And Maggie's unexpected charm, elegance, and religious devotion makes her the perfect partner in lies..."--